Enoxaparin-induced unilateral hemotympanum. Issue 5 (July 2015) - Aydin, Umit; Asik, M. Burak; Gokgoz, M. Cemal; Karakoc, Omer
Abstract : Hemotympanum is defined as the presence of blood in the middle ear cavity. It is commonly associated with skull fractures. Spontaneous hemotympanum secondary to anticoagulant therapy is extremely rare. Herein, we report the first case of a 51-year-old woman with right spontaneous hemotympanum related to the use of enoxaparin. Complete resolution of signs and symptoms was accomplished by conservative management. Close follow-up is important to assure resolution and reduce long-term sequelae. The use of anticoagulants should be considered in the differential diagnosis of hemotympanum. This is also a good case for clinicians to be mindful about hemorrhagic complications of anticoagulant treatment.